A Second Domesday? : the Hundred Rolls of 1279-80. - Raban, Sandra (Oxford University Press, UK, 2004)
This is the first comprehensive study of the 1279-80 hundred rolls, one of the most important sources for later thirteenth century England. Raban puts the rolls in their historical context, looks at the way in which the inquiry was conducted and questions whether or not it was conceived as a second Domesday. Based on the latest knowledge of the returns, this will be an indispensable working tool for historians. - ;The 1279-80 hundred rolls are one of the most important sources for later thirteenth century England, yet this is the first comprehensive study of the inquiry which brought them into.